A high capacity polymeric micelle of paclitaxel: Implication of high dose drug therapy to safety and in vivo anti-cancer activity. (September 2016) - He, Zhijian; Wan, Xiaomeng; Schulz, Anita; Bludau, Herdis; Dobrovolskaia, Marina A.; Stern, Stephan T.; Montgomery, Stephanie A.; Yuan, Hong; Li, Zibo; Alakhova, Daria; Sokolsky, Marina; Darr, David B.; et al.
Abstract: The poor solubility of paclitaxel (PTX), the commercially most successful anticancer drug, has long been hampering the development of suitable formulations. Here, we present translational evaluation of a nanoformulation of PTX, which is characterized by a facile preparation, extraordinary high drug loading of 50% wt. and PTX solubility of up to 45 g/L, excellent shelf stability and controllable, sub-100 nm size. We observe favorable in vitro and in vivo safety profiles and a higher maximum tolerated dose compared to clinically approved formulations. Pharmacokinetic analysis reveals that the higher dose administered leads to a higher exposure of the tumor to PTX. As a result, we observed improved therapeutic outcome in orthotopic tumor models including particularly faithful and aggressive "T11" mouse claudin-low breast cancer orthotopic, syngeneic transplants. The promising preclinical data on the presented PTX nanoformulation showcase the need to investigate new excipients and is a robust basis to translate into clinical trials.